High coherence collapse of a hybrid III–V/Si semiconductor laser with a large quality factor. (10th April 2020) - Gomez, S; Huang, H; Duan, J; Combrié, S; Shen, A; Baili, G; de Rossi, A; Grillot, F
Abstract: The high-speed dynamics of a hybrid distributed feedback semiconductor laser heterogeneously integrated onto silicon is experimentally investigated in the presence of external optical feedback. The laser fabrication relies on a proper modal engineering in which light is generated in the III–V material and stored in the low-loss silicon region in order to substantially enhance the quality factor of the cavity resonator. In this work, the hybrid laser is found to be insensitive to parasitic reflections leading to a 10 Gbps floor-free transmission with a power penalty no greater than 1.5 dB at room temperature. As a conclusion, owing to the large quality factor, a high coherence collapse level is unveiled in such laser indicating its vast potential to serve as an alternative solution for the development of isolator-free applications in future photonics integrated circuits. A qualitative interpretation is also provided by linking the standard feedback equations to the quality factor of the resonator.